2020
DOI: 10.2147/oaem.s266702
|View full text |Cite
|
Sign up to set email alerts
|

<p>COVID-19 Emergency Department Protocols: Experience of Protocol Implementation Through in-situ Simulation</p>

Abstract: Purpose: During the outbreak of Coronavirus disease of 2019 (COVID-19), the preparedness of emergency departments (EDs) for triaging of the patients and safety of staff is of utmost importance. The aim of our study was to develop and implement COVID-19 ED triage and protected intubation protocols for COVID-19 patients with in-situ simulation (ISS) training. The latent safety threats (LST) detection also served as a platform to test new system amendments and refine the protocols and workflows with infection con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…LST evaluation 24 (25) Chan et al 31 Hamman et al 59 Hamman et al 60 Hunt et al 44 Kerner et al 62 Kobayashi et al 52 Kobayashi et al 63 O'Leary et al 64 Patterson et al 10 Shrestha et al 34 Theilen et al 41 Ullman et al 67 Walsh et al 68 Whitfill et al 69 Zimmermann et al 70 Bradley et al 71 Couto et al 36 Geis et al 72 Lakissian et al 73 Shah et al 37 Wong et al 74 Petrosoniak et al 75 Aljahany et al 76 Zern et al 77 Shrestha et al 78 Gray et al 42 Others (survey, qualitative analysis) Bischof et al 80 Burke et al 81 Couto et al 13 Davison et al 82 Gangadharan et al 83 Gundrosen et al 84 Hunt et al 44 Mannenbach et al 85 Meurling et al 86 O'Leary et al 87 Shrestha et al 34 Sørensen et al 88 Ullman et al 67 Katznelson et al 89 KP 2: knowledge and skills 10 Walsh et al 68 Bradley et al 71 Thomas et al 90 Lemke et al 91 Kalidindi et al…”
Section: Satefy-related Parameters N (%) Referencesmentioning
confidence: 99%
“…LST evaluation 24 (25) Chan et al 31 Hamman et al 59 Hamman et al 60 Hunt et al 44 Kerner et al 62 Kobayashi et al 52 Kobayashi et al 63 O'Leary et al 64 Patterson et al 10 Shrestha et al 34 Theilen et al 41 Ullman et al 67 Walsh et al 68 Whitfill et al 69 Zimmermann et al 70 Bradley et al 71 Couto et al 36 Geis et al 72 Lakissian et al 73 Shah et al 37 Wong et al 74 Petrosoniak et al 75 Aljahany et al 76 Zern et al 77 Shrestha et al 78 Gray et al 42 Others (survey, qualitative analysis) Bischof et al 80 Burke et al 81 Couto et al 13 Davison et al 82 Gangadharan et al 83 Gundrosen et al 84 Hunt et al 44 Mannenbach et al 85 Meurling et al 86 O'Leary et al 87 Shrestha et al 34 Sørensen et al 88 Ullman et al 67 Katznelson et al 89 KP 2: knowledge and skills 10 Walsh et al 68 Bradley et al 71 Thomas et al 90 Lemke et al 91 Kalidindi et al…”
Section: Satefy-related Parameters N (%) Referencesmentioning
confidence: 99%
“…Our study represents a novel attempt to describe the experiences of healthcare professionals tasked with adjusting to a rapidly disseminated protocol during the COVID-19 pandemic. These results contribute to a small but growing body of literature comprising previous studies describing the implementation, operation, safety, and efficacy of emergency response intubation teams [ 3 5 , 33 35 ]. Our findings highlight the need for evaluating the subjective experience of healthcare providers when transitioning to new models of care in response to emergencies.…”
Section: Discussionmentioning
confidence: 64%
“…[4][5][6][7] Our data also corroborated studies that showed that simulation was essential for developing, testing, refining and implementing new workflows and protocols in healthcare. 8,10,11,18,19 This was also essential in the context of the COVID-19 pandemic, in which we trained healthcare professionals on the new protocol for safe and effective care of patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In situ simulation is a fast and efficient way for training a multidisciplinary team because training takes place during the team's hours of service, using the workplace resources. 19 In this study, we decided to use questions with very short answers. Use of questions of this nature made it possible to assess the participants' knowledge without giving any clues about the correct answer.…”
Section: Discussionmentioning
confidence: 99%